Intrinsic brain abnormalities in female major depressive disorder patients with childhood trauma: A resting-state functional magnetic resonance imaging study - Chen, Juran; Luo, Qianyi; Li, Yuhong; Wu, Zhiyao; Lin, Xinyi; Yao, Jiazheng; Yu, Huiwen; Nie, Huiqin; Du, Yingying; Peng, Hongjun; Wu, Huawang (Frontiers in Neuroscience, 2022)
Objective: Childhood trauma is a momentous predictor of major depressive disorder (MDD). Female are more likely to suffer from MDD. However, the neural basis underlying female MDD with childhood trauma remain unclear. Thus, our aim was to ascertain the specific brain regions linked with female MDD and childhood trauma. Methods: 16 female MDD patients with childhood trauma, 16 female MDD patients without childhood trauma and 20 matched healthy controls were recruited. Entire participants were conducted resting-state functional magnetic resonance imaging scanning. Regional brain activity was evaluated with amplitude of low-frequency fluctuation (ALFF). Further functional connectivity analysis was done on areas with altered ALFF to explore the alteration in functional connectivity patterns. Results: Increased ALFF were discovered between MDD with childhood trauma and MDD without childhood trauma in left middle frontal gyrus and the right postcentral gyrus. The areas with significant ALFF discrepancies were selected as seed in FC analyses. Increased FC was discovered among left MFG seed and left putamen gyrus and right putamen gyrus, respectively. Moreover, ALFF values were correlated with childhood trauma severity. Conclusion: Overall, our findings revealed the abnormal intrinsic brain activity and FC pattern in female MDD with childhood trauma, providing insights into the pathophysiology of female MDD with childhood trauma.